Pertumbuhan Dan Produksi Genotipe Bawang Merah (Allium ascalonicum L.) Lokal Samosir Generasi Ke Enam (M1V6) Hasil Iradiasi Sinar Gamma di Dataran Tinggi Samosir - Daniel C Sipangkar; Mariati; Meirani (Jurnal Pertanian Tropik, 2018)
The objective of this research was to identify the growth and yield of sixth-generation (M1V6) of local Samosir shallot, irradiated by gamma. The research was conducted at Rianiate village, Pangururan Samosir district at altitude ± 1164 meters above sea level, which began from July up to October 2016. This study used an augmented design with 8 levels of irradiated dosage (0; 1; 2; 3; 4; 5; 6; 8) Gy. The observes parameters were plant length, number of leaves, number of tillers, bulb number, bulb diameter, bulb fresh weight, and bulb dry weight after twice harvesting. The study result showed that population as a result of dosage irradiation at 5 Gy were significant difference compared to control plant populations with a lower mean value for the plant length, the number of leaves, the number of tillers and fresh weight while on tuber diameter, population of dosage irradiation 8 Gy were significant difference compared to the control population.